Good Corporate Governance Through Capital Structure Analysis to Improve Profitability - Sari, Nurdela; Zaenuddin, Ksatriawan (Unit Publikasi Ilmiah Perkumpulan Intelektual Madani Indonesia, 2025)
In an increasingly competitive business environment, the implementation of Good Corporate Governance (GCG) has become an important factor in maintaining business sustainability and increasing company profitability. This study aims to analyze the effect of capital structure on the profitability of PT Suryamas Dutamakmur Tbk from a GCG perspective. The method used is quantitative descriptive with secondary data in the form of company financial reports for the 2017–2020 period. Capital structure is measured through the Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), and Long Term Debt to Equity Ratio (LDER), while profitability is measured using Return on Assets (ROA) and Return on Equity (ROE). The results show that during the 2017–2020 period, there was a downward trend in leverage ratios (DAR, DER, LDER) followed by an increase in profitability ratios (ROA, ROE), especially in 2020. This indicates that reducing dependence on debt has a positive impact on financial efficiency and increases company profits. From a GCG perspective, a conservative capital structure policy reflects the principles of prudential governance and accountability in financial management. However, profit fluctuations in 2018 indicate the need to improve operational efficiency so that debt control policies also create added value. With consistent implementation of GCG, PT Suryamas Dutamakmur Tbk has the potential to strengthen its financial stability and increase profitability in a sustainable manner.